17β-Estradiol Attenuates Poststroke Depression and Increases Neurogenesis in Female Ovariectomized Rats. (7th November 2013) - Cheng, Yifan; Su, Qiaoer; Shao, Bei; Cheng, Jianhua; Wang, Hong; Wang, Liuqing; Lin, Zhenzhen; Ruan, Linhui; ZhuGe, Qichuan; Jin, Kunlin
Abstract : Studies have linked neurogenesis to the beneficial actions of specific antidepressants. However, whether 17 β -estradiol (E2 ), an antidepressant, can ameliorate poststroke depression (PSD) and whether E2 -mediated improvement of PSD is associated with neurogenesis are largely unexplored. In the present study, we found that depressive-like behaviors were observed at the first week after focal ischemic stroke in female ovariectomized (OVX) rats, as measured by sucrose preference and open field test, suggesting that focal cerebral ischemia could induce PSD. Three weeks after middle cerebral artery occlusion (MCAO), rats were treated with E2 for consecutive 14 days. We found that E2 -treated rats had significantly improving ischemia-induced depression-like behaviors in the forced-swimming test and sucrose preference test, compared to vehicle-treated group. In addition, we also found that BrdU- and doublecortin (DCX)-positive cells in the dentate gyrus of the hippocampus and the subventricular zone (SVZ) were significantly increased in ischemic rats after E2 treatment, compared to vehicle-treated group. Our data suggest that focal cerebral ischemia can induce PSD, and E2 can ameliorate PSD. In addition, newborn neurons in the hippocampus may play an important role in E2 -mediated antidepressant like effect after ischemic stroke.